Optimalisasi sistem pengarsipan dokumen untuk meningkatkan efisiensi pelayanan nasabah di PT Bank Pembangunan Daerah Jawa Timur Tbk (Bank Jatim) - Ali Muhajir; Fitri Dwi Anggraeni; S. Zesivania Mar’atussholihah (Nur Science Institute, 2026)
This community service activity was conducted to support the orderly implementation of a document archiving system to enhance the effectiveness of customer administrative services at Bank Jatim. The main issue addressed concerns the importance of maintaining consistency in the implementation of archiving procedures to ensure that document management remains organized, easily accessible, and supportive of smooth administrative processes. The method employed was a descriptive approach, with participatory involvement through students' direct engagement in administrative activities in accordance with institutional procedures. The activity was carried out in stages: observation, administrative participation, documentation, and descriptive evaluation of the implementation of archive management. The results indicate that the implemented archiving system has supported administrative orderliness by classifying documents, storing archives, and grouping documents in accordance with established procedures. The success indicators of the activity were assessed through document organization, consistency of archive classification, ease of document access, and the administrative workflow observed during implementation. The findings indicate that participatory involvement in administrative activities can support the orderly implementation of archive management and contribute to the effectiveness of administrative services in the banking environment.